Social limits to growth - Hirsch, Fred. (London Routledge, 1995)
The promise of economic growth which has dominated society for so long has reached an impasse. In his classic analysis, Fred Hirsch argued that the causes of this were essentially social rather than physical. Affluence brings its own problems. As societies become richer, an increasing proportion of the extra goods and services created are not available to everybody. Material affluence does not make for a better society.
Includes index
Keywords: Economic development--Social aspects